ANALISIS PENGARUH SERTIFIKASI ISO 9000 TERHADAP RASIO RETURN ON INVESTMENTS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - CENDRAWATI CENDRAWATI; MELINDA HARYANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
This study analyzes the impact of ISO 9000 certification on operating performance measured by Return on Investments (ROI) ratio. Specifically, this study researches whether there is a difference in ROI between certified companies and non - certified companies and whether there is a difference in ROI before and after the certification. Two components of ROI, Operating Profit Margin (OPM) and Operating Assets Turnover (OAT) serve to explain the difference in ROI. Data was taken from a sample of companies listed in Indonesia Stock Exchange. The sample companies were selected using purposive sampling based on some criterias. Data for each companies was obtained from internet and stock exchange information center. Statistical method used to analyze the data was hypothesis test for comparing means (t-test for normally distributed data and non - parametric test for not normally distributed data). The results show that there is no difference in ROI between certified companies and non - certified companies, while there is a difference in ROI before and after the certification where ROI tends to decrease after certification due to increased costs.